UPAYA INTERVENSI EDUKASI DAN DETEKSI DINI DIABETES MELLITUS SEBAGAI UPAYA PENCEGAHAN KOMPLIKASI PADA LANSIA - Addiarto, Widya; Yunita, Rizka (Journal of Health Innovation and Community Services, 2026)
The community service program was conducted to improve elderly health through early screening and education on Diabetes Mellitus (DM) in Karangbong Village, Pajarakan District, Probolinggo Regency. A total of 25 participants aged 55–70 years underwent random blood glucose (RBG) testing and health education interventions. The results showed that 60% had normal glucose levels, while 36% were categorized as prediabetes and 4% as DM. The educational intervention significantly enhanced knowledge, with the proportion of participants in the “good” category increasing from 20% to 44% and the “poor” category decreasing from 52% to 20%. Nevertheless, 56% of participants remained at moderate to poor knowledge levels, indicating the need for more interactive educational methods, family involvement, and continuous mentoring. This program demonstrates that early screening is effective in identifying health risks among the elderly, while lifestyle modification, regular monitoring, and community support are crucial to prevent complications. The model can be adapted for elderly health services such as posyandu lansia to strengthen promotive and preventive strategies against chronic diseases.